Innovative human resources management: Key competencies expected from hospitality graduates in Ghana - Commey, Vida; Kokt, Desere; Hattingh, Johan (Goodwood Publishing, 2020)
Purpose: The study aimed to determine the key competencies required from hospitality graduates from the hospitality industry perspective. Research Methodology: The study adopted a qualitative research approach. Overall, 43 hotel managers in the Ghanaian hospitality industry were conveniently sampled. Data were collected using a structured survey questionnaire. The study used Statistical Package for Social Sciences (IBM SPSS) version 23 to analysed data collected. Results: Results from the study indicate that the “key competencies” required from hospitality graduates from the industry perspective include good inter-personal skills, innovation and ability to think of new ways of doing things, ability to maintain professional standards, customer-oriented, critical thinking ability, self-motivation, friendly and approachable, good communication skills. Conclusions: This study highlights key competencies required from hospitality graduates, including communication, innovation, and customer orientation, emphasizing the need for curricula to align with industry demands and continuous collaboration between academia and the hospitality sector. Limitations: The study focused only on hospitality employers in Ghana; therefore, findings from the study cannot be generalised to other hospitality employers in different country. Contributions: The study emphasises the need for hospitality educational institutions in Ghana to assess the tourism and hospitality industry's competencies to produce graduates who will fit in the job market.